Analytical method improvement, formation and mitigation of 2-MCPD, 3-MCPD esters and glycidyl ester in palm oil-containing foods during baking process - Goh, Kok Ming (2019)
Based on the recent European Food Safety Authority Journal 2016, monochloropropanediol (MCPD) ester and glycidyl ester (GE) are critical contaminants predominantly found in palm oil and palm-based food products. MCPD ester is regarded as a nongenotoxic carcinogen, while GE is a genotoxic carcinogen. It is important to improve the current analysis method (with rapid method) and study the formation and mitigation of MCPD ester and GE in baked goods. In this study, it is aimed to evaluate the analysis method (GC-MS/MS and FTIR), formation and mitigation of the formation of 3- and 2-MCPD esters and GE in related baking products and during the baking process. The experiment was divided into four parts. First, the difference in the performance between selected ion monitoring (SIM) and multiple reaction monitoring (MRM) detection mode was assessed. In MRM mode, the limit of detection (LOD) of 3- and 2-MCPD ester was 0.01 mg/kg while the limit of quantification (LOQ) was 0.05 mg/kg. In addition, the limit of detection (LOD) and the limit of quantification (LOQ) of GE were 0.024 and 0.06 mg/kg, respectively. MRM mode showed better repeatability in area ratio and recovery with relative standard deviation (RSD %) < 5% for 2- and 3-MCPD ester. Quantification of 22 food samples using MRM mode showed higher repeatability and reliability compared to SIM, which fluctuated as high as 50% RSD. Second, a baking process was simulated using commercial margarine (control), palm olein, palm mid-fraction, and soft and hard stearin, baked at different temperatures (160, 180 and 200 ℃) for 20 min. The results showed soft stearin and palm olein delivered a similar volume, surface color, and texture to the finished product compared to the control. An elevated baking temperature significantly (p<0.05) increased the hardness and chewiness, and lowered the springiness of the finished products. The content of MCPD esters from the cake samples was insignificant (p>0.05) throughout the experiment, but GE was significantly degraded (p<0.05) when a baking temperature of 200 ℃ was used. Third, palm olein and soft stearin were fortified with antioxidants, BHA, rosemary and tocopherol at single dosage (200 mg/kg) and in combinations (BHA at 200 mg/kg with rosemary or tocopherol at 400, 800 and 1200 mg/kg). Electron spin resonance spectrometry measurement showed that antioxidant was effective to reduce the radical formation. MCPD esters and GE were significantly lower (p<0.05) when a higher concentration of natural antioxidants was used. Antioxidants were effective to inhibit oxidation, as well as formation of free fatty acid and unstable 1,2-diacylglycerol. Finally, a rapid prediction of MCPD ester and GE was performed using Fourier transform infrared (FTIR) spectroscopy coupled with chemometrics analysis. The results showed a consensus model was able to predict MCPD ester (R2 = 0.91) and GE (R2 = 0.94) at high accuracy. Among the established individual models, cubist and random forest models performed better to predict MCPD ester, while random forest and neural network model performed equally to predict GE. In conclusion, MCPD esters and GE quantification performed optimally using MRM detection; baking temperature strongly affected the quality and GE content of baked goods; antioxidant in combination was able to control oxidation and MCPD ester and/or GE formation; and finally, a consensus model served as a rapid alternate analysis method in MCPD esters and GE predictions.